2019
DOI: 10.22364/bjmc.2019.7.4.05
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Analysis of Latvian CORS Stadions

Abstract: This paper considers the origin of Latvian Coordinate System LKS-92 definition which was based on two GNSS campaigns in 1992 and 2003. There are two continuously operating reference networks in Latvia: LatPos and EUPOS ®-Riga. GNSS stations of these networks have fixed coordinate values in LKS-92. At the Institute of Geodesy and Geoinformatics of the University of Latvia both LatPos and EUPOS ®-Riga station daily coordinate values are calculated. The coordinate differences between epochs 1989.0 and 2018.5 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…The Global Navigation Satellite System-Continuously Operating Reference Station (GNSS -CORS) network stations that are designed with excellent spatial density and distribution are used for various geodetic and non-geodetic applications [1][2][3][4][5]. The estimation of seasonal changes of CORS positions plays an extremely important role, since it can impact the final estimates, particularly the site velocity [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The Global Navigation Satellite System-Continuously Operating Reference Station (GNSS -CORS) network stations that are designed with excellent spatial density and distribution are used for various geodetic and non-geodetic applications [1][2][3][4][5]. The estimation of seasonal changes of CORS positions plays an extremely important role, since it can impact the final estimates, particularly the site velocity [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to characterise land uplift effect in Latvia by analysing precise levelling data have been made earlier [13,14]. Latvian continuously operating reference station (CORS) rates (or velocities) has been previously analysed [15,16] and have shown that GIA effect rates up to about 2 mm/yr in the vertical direction in the north-western part of Latvia. However, no detailed analysis of seasonal variations and noise characteristics of the Latvian CORS have been performed up till now.…”
Section: Introductionmentioning
confidence: 99%